Impact of COVID-19 pandemic social restriction measures on people with rheumatic and musculoskeletal diseases in the UK: a mixed-methods study. Issue 6 (2nd June 2021) - Smith, Toby O; Belderson, Pippa; Dainty, Jack R; Birt, Linda; Durrant, Karen; Chipping, Jacqueline R; Tsigarides, Jordan; Yates, Max; Naughton, Felix; Werry, Sarah; Notley, Caitlin; Shepstone, Lee; et al.
Abstract : Objectives: To determine the impact of COVID-19 pandemic social restriction measures on people with rheumatic and musculoskeletal diseases (RMDs) and to explore how people adapted to these measures over time. Design: Mixed-methods investigation comprising a national online longitudinal survey and embedded qualitative study. Setting: UK online survey and interviews with community-dwelling individuals in the East of England. Participants: People in the UK with RMDs were invited to participate in an online survey. A subsection of respondents were invited to participate in the embedded qualitative study. Primary and secondary outcome measures: The online survey, completed fortnightly over 10 weeks from April 2020 to August 2020, investigated changes in symptoms, social isolation and loneliness, resilience and optimism. Qualitative interviews were undertaken assessing participant's perspectives on changes in symptoms, exercising, managing instrumental tasks such a shopping, medication and treatment regimens and how they experienced changes in their social networks. Results: 703 people with RMDs completed the online survey. These people frequently reported a deterioration in symptoms as a result of COVID-19 pandemic social restrictions (52% reported increase vs 6% reported a decrease). This was significantly worse for those aged 18–60 years compared with older participants (p=0.017). The qualitative findings from 26 individuals with RMDs suggest that the greatest change in daily life was experienced by those in employment. Although some retired people reported reduced opportunity for exercise outside their homes, they did not face the many competing demands experienced by employed people and people with children at home. Conclusions: People with RMDs reported a deterioration in symptoms when COVID-19 pandemic social restriction measures were enforced. This was worse for working-aged people. Consideration of this at-risk group, specifically for the promotion of physical activity, changing home-working practices and awareness of healthcare provision is important, as social restrictions continue in the UK.